EFFICIENCY IN PLYWOOD FABRICATION: STRATEGIC OPTIMIZATION OF LAMINATED PROCESSES - Chen, Xiao Ming; Xu, Lei Hong (International Journal of Civil Engineering and Architecture and Real Estate, 2024)
To align with national policies aimed at fostering sustainable and healthy growth in the construction industry, Shandong Province introduced the "Shandong Prefabricated Construction Development Plan (2018-2025)." This plan underscores the importance of propelling the sustainable and healthy advancement of prefabricated buildings. Furthermore, to facilitate the widespread adoption of prefabricated construction methods and foster the modernization of the construction industry, the Binzhou Housing and Urban-Rural Development Bureau, in collaboration with other relevant authorities, issued "Opinions on Further Promoting the Development of Prefabricated Buildings." These opinions lay out essential guidelines, including development tasks, approval processes, supervision mechanisms, policy incentives, and employment security measures, all aimed at accelerating the growth of prefabricated buildings. Prefabricated construction stands as a pivotal catalyst for transforming the old and new energies within the construction industry. It offers an ecofriendly, low-energy building approach and has garnered the attention of governmental bodies at all administrative levels. This research endeavors to explore and enhance the production processes and equipment involved in prefabricated component manufacturing. This, in turn, represents a critical step in advancing the development of prefabricated buildings and facilitating the transformation and upgradation of the construction industry.